2022
DOI: 10.1007/s00415-022-11252-2
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-dl-leucine in cerebellar ataxia ([18F]-FDG-PET study): how does a cerebellar disorder influence cortical sensorimotor networks?

Abstract: Objective The aim of the study was to deepen our insights into central compensatory processes of brain networks in patients with cerebellar ataxia (CA) before and with treatment with acetyl-dl-leucine (AL) by means of resting-state [18F]-FDG-PET brain imaging. Methods Retrospective analyses of [18F]-FDG-PET data in 22 patients with CA (with vestibular and ocular motor disturbances) of different etiologies who were scanned before (PET A) and on AL treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A case series of patients with cerebellar ataxia of various origins treated with ADLL suggested a clinically significant benefit of the treatment [221,222] that has also been supported by neuro-metabolic studies [223][224][225]. However, the evidence for the efficacy of ADLL is somewhat contradictory with a negative placebo-controlled clinical trial that failed to show the improvement in cerebellar ataxia signs and symptoms [226].…”
Section: Acetyl-l-leucinementioning
confidence: 97%
“…A case series of patients with cerebellar ataxia of various origins treated with ADLL suggested a clinically significant benefit of the treatment [221,222] that has also been supported by neuro-metabolic studies [223][224][225]. However, the evidence for the efficacy of ADLL is somewhat contradictory with a negative placebo-controlled clinical trial that failed to show the improvement in cerebellar ataxia signs and symptoms [226].…”
Section: Acetyl-l-leucinementioning
confidence: 97%
“…N -acetyl- l -leucine, a modified amino acid, is used in the treatment of vertigo. Its mechanism of action involves the activation of cerebral glucose metabolism in the cerebellum and other regions of the brain 119 , 120 . Notably, N -acetyl- l -leucine has also shown promise in delaying disease progression and extending the lifespan of Npc1 −/− mice 121 .…”
Section: N -Acetyl- L -Leucinementioning
confidence: 99%
“…Such compensation mechanisms have been already proposed in several neurological diseases. For example, Becker-Bense et al ( 8 ) revealed a compensatory strategy in the multisensory visual network of adult ataxic patients with vestibular and oculomotor symptoms, while a compensative role played by the cerebellum on the basal ganglia dysfunctions has been observed in patients with Parkinson’s disease ( 9 , 10 ). Recently, a wider number of works has pointed out the fundamental role of the cerebellum-basal ganglia interplay for balance, motor control and coordination ( 11 ).…”
Section: Introductionmentioning
confidence: 99%